Preparing the Future Public Health Workforce: Fostering Global Citizenship Through the Relational Employability Framework—Insights from Two Case Studies - Elizabeth J. Cook; Sally-Anne Doherty; Ruth Wallace (Education Sciences)
A well-prepared public health workforce is essential for reducing disease burdens and improving population health, necessitating an education that addresses global and complex challenges. This paper explores the integration of the Relational Employability Framework in public health education as a tool to foster critical reflection and cultivate global citizenship among students and graduates. Global citizenship encompasses the social, political, environmental and economic actions of globally conscious individuals and communities, recognising that individuals operate within diverse local and global networks. Relational employability expands traditional notions of graduate employability, incorporating not only foundational career development and human interactions but also connections with more-than-human elements, including ecologies, technologies and materials. Our research, conducted at Edith Cowan University in Perth, Western Australia, involved two case studies using qualitative interviews. Case Study 1, drawn from the Cook’s doctoral research, explored student experiences with the Relational Employability Framework within an undergraduate capstone unit. Case Study 2, a school-funded project, gathered graduate perspectives to inform ongoing curriculum development. The findings indicate that the Relational Employability Framework can help support the development of global citizenship through critical reflective practice, as students reported improved ability to engage with diverse perspectives and societal challenges, and graduates highlighted the framework’s role in supporting ethical, evidence-based practice in professional contexts. Additionally, the framework supported the development of a reflective mindset, which graduates said helped them make informed, value-based career decisions, thus advancing their professional growth. This study suggests that adopting a relational employability approach can prepare globally competent and reflective public health professionals and recommends its implementation across health and higher education.